Syllabus Design for Tertiary Level Students in Bahasa Inggris Niaga Course - Masriatus Sholikhah; Afi Ni’amah (JET ADI BUANA, 2022)
Teaching English in non-English department needs meticulous preparation since it is given integrative in four skills within restricted credit hours, 4 SKS. Students of Economic Department need to be prepared as profound entrepreneur that they are keen on creating occupations and other professions but teacher solely. The research was aimed to design topics and methods in syllabus of Bahasa Inggris Niaga course. This research was set out by implementing ADDIE in designing the syllabus for tertiary students who major in economic department. Analysis as the first step was done by doing interview and giving questionnaire. The result indicated ten significant topics and seven relevant methods in designing Bahasa Inggris Niaga syllabus. They were designed by concerning on the undergraduate students’ necessity in pre intermediate level.